Levels of Obedience According to a Javanese Tafsir: An Analysis of Bakri Syahid's Tafsir Al-Huda - Sulchan Ainur Ramadhan; Alfiyatul Azizah; Kharis Nugroho; Yeti Dahliana; Ahmad Nurrohim (Jurnal Studi Al-Qur'an, 2025)
This study discusses the concept of obedience according to Bakri Syahid in Tafsir Al-Huda, a Javanese interpretation. This study examines how Bakri Syahid interprets and defines obedience in various speech and Javanese vocabulary levels, from Ngoko to krama. This interpretation shows the importance of obedience, as obedience is passive and involves deep appreciation and sincerity. Through a qualitative approach and library research method, the author examines 54 verses of the Qur'an containing the word and its derivations ṭā‘ah and identifies five levels of obedience, from the lowest (Ngrujuki) to the highest (Ngestokaken Dhawuh). The author also examines the meaning of each interpretation of ṭā‘ah in Javanese through several dictionaries and books on Javanese grammar. In addition, in studying the verses, the author considers the Asbabun Nuzul verses and Ibn Kathir's interpretation as a comparison to make this research as objective as possible. This research concludes that obedience, according to Bakri Syahid, involves seriousness, conformity between words, heart, and deeds, sincerity, conformity to the rules, readiness in all circumstances, consistency, love, and respect in carrying out Allah's commands.